Routine use of antenatal nonstress tests in pregnant women with diabetes–What is the practice?. (May 2020) - Jørgensen, Isabella L.; Vestgaard, Marianne; Ásbjörnsdóttir, Björg; Mathiesen, Elisabeth R.; Damm, Peter
Abstract: Objective: Pregnancies complicated by maternal preexisting diabetes have a 4-5-fold increased risk of stillbirth, and consequently routine antenatal nonstress testing (NST) was implemented into clinical practice decades ago. Though, international guidelines lack consensus and recommend anything from twice weekly testing from 32 weeks to once weekly testing from 38 weeks. The objective of this study was to examine how routine antenatal NST was used in centers with specific interest and dedication in the care of pregnant women with preexisting diabetes. Study Design: An electronic survey concerning the routine use of antenatal NST was sent to members of the European Diabetic Pregnancy Study Group (DPSG) between October 2016 and January 2017, representing in total 55 centers in 26 countries taking care of pregnant women with diabetes. Results: Answers from 38 centers (69.1 % (38/55)) in 22 countries were received. Based on real world information from these primarily European centers, anything from avoiding routine antenatal NST to testing twice weekly from early in third trimester in women with preexisting diabetes was reported. NST was commonly used (71.1 % of centers) if insulin treatment was needed. NST was also used among diet treated women with type 2 diabetes in several places. The use varied markedly within and between countries. The most common practice was routine NST once weekly from 32 weeks. Conclusion: Among pregnant women with preexisting diabetes, routine antenatal testing practice with NST differs considerably both within and between countries. Studies examining the cost benefit of routine antenatal NST in pregnancies in women with the different types of diabetes are needed.